Escaping alpha-particle monitor for burning plasmas. (29th June 2018) - Kiptily, V.G.; Shevelev, A.E.; Goloborodko, V.; Kocan, M.; Veshchev, E.; Craciunescu, T.; Khilkevitch, E.M.; Lengar, I.; Polunovsky, I.A.; Schoepf, K.; Soare, S.; Yavorskij, V.; et al.
Abstract: This paper presents a diagnostic system, gamma-ray alpha-particle monitor (GRAM), for continuous monitoring of deuterium–tritium fusion α -particles in the MeV energy range escaped from the plasma to the first wall. The diagnostic is based on the detection of γ -rays produced in nuclear reactions. The reactions 9 Be( α, nγ ) 12 C and 10 B( α, pγ ) 13 C have been selected. For that purpose, Be- or 10 B-target is placed on the first wall, where the alphas are expected to be mostly lost. Striking the target, the lost alphas generate specific γ -rays, if their energy E α > 1.5 MeV. To measure this γ -ray emission, the target should be in the field of view of a collimated detector, which is protected from neutrons and background gammas. The calibrated detector could deliver absolute values of the lost α -particle flux with a temporal resolution depending on intensity of losses. A high-performance γ -ray spectrometer with a novel architecture, GRITER, is proposed to be used in GRAM. It consists of a stack of the optically isolated high- Z fast scintillators with independent signal readout. GRITER is supposed to be operated at count-rates substantially exceeding the capability of a single crystal detector of the same size. The GRAM diagnostic system consists of two identical spectrometers, which measure both γ -rays due to α -particle loss and γ -ray background ensuring reliable data in a harsh reactor environment. GRAM could be tested during the non-DT plasma operation monitoring lost DD fusion products, neutral beam heating D-ions ( E D > 0.5 MeV) and ICRF accelerated H- and 3 He-ions through the detection of γ -rays resulting from nuclear reactions. The use of GRAM on JET and ITER, including events with extremely high loss rates, is discussed.